Introducción al Taller y Repositorios de Nueva Generación COAR - Mennielli, Michele (2018)
Contenidos: 1. Who we are and who are you? 2. International context, interoperability and next generation repositories. 3. Dspace technical implementation. 4. Dspace-CRIS tutorial. 5. Building a community of practice for repositories in Peru